Dampak Tata Kelola Bank Syariah Terhadap Kepatuhan Syariah Berbasis Maqashid Syariah - Rifqi Muhammad; Hapsari Yuni Oktaviyanti (Akademi Akuntansi YKPN Yogyakarta, 2020)
This study aims to determine the effect of Good Corporate Governance as measured by the number of sharia supervisory boards, sharia supervisory board meetings, number of board of directors, board of directors meetings, number of board of commissioners, board of commissioners meeting on the performance of sharia maqashid. The sample used in this study is Full-fledge sharia banks in Indonesia based on sharia banking statistics published by the Financial Services Authority as of July 2019. The study was conducted based on an analysis of 72 annual reports and GCG reports obtained from 12 Sharia Commercial Banks in 2013 - 2018. The results of this study indicate that the variables of the board of directors' meeting significantly influence the performance of the Maqashid syariah. While the variable number of sharia supervisory boards, sharia supervisory board meetings, number of board of directors, number of board of commissioners and board of commissioners meeting on maqashid syariah performance.